Vaccination with a Paramyosin-Based Multi-Epitope Vaccine Elicits Significant Protective Immunity against Trichinella spiralis Infection in Mice - Gu, Yuan; Sun, Ximeng; Li, Bo; Huang, Jingjing; Zhan, Bin; Zhu, Xinping (Frontiers in Microbiology, 2017)
Trichinellosis is a worldwide zoonosis and remains a serious public health problem. Interrupting parasite transmission via vaccination of livestocks with a potent vaccine is a practical approach to prevent human Trichinellosis. Our previous studies have identified that paramyosin of Trichinella spiralis (Ts-Pmy) is a good vaccine candidate against Trichinellosis. In this study, a novel multi-epitope vaccine (MEP) was constructed by using four CD4+ T cell epitopes (P2, P3, P4 and P5) and one B cell epitope (YX1) from Ts-Pmy and expressed as a soluble recombinant protein (rMEP) in E. coli. Mice immunized with rMEP vaccine produced significant higher muscle larval reduction (55.4%) than that induced by immunization of parental rTs-Pmy (34.4%) against T. spiralis infection. The better protection is associated with rMEP induced high levels of anti-rMEP specific IgG and subclass IgG1 / IgG2a, elevated T cell proliferation of splenocytes and secretion of IFN-γ, IL-4 and IL-5. The cellular response to individual T cell epitope also showed that splenocytes from mice immunized with rMEP strongly response to the stimulation of synthetic epitope peptide P2, P3 and P4, but not to P5, suggesting that most of T cell epitopes are exposed and processed well during immunization that may contribute to the high protection induced by the immunization of rMEP. This study implies that epitope vaccine is a promising approach for the development of vaccines against Trichinellosis.